1974
DOI: 10.1111/j.1469-8137.1974.tb04607.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Responses to Vesiculararbuscular Mycorrhiza

Abstract: SUMMARYLight and temperature greatly influenced the development of vesicular-arbuscular mycorrhiza and growth of onions in a phosphate-deficient soil. There were more large arbuscules and host growth was stimulated more with 25,000 lux than with 13,000 lux at 23° C and in a 14-23° C diurnal cycle. At 14° C and 13,000 lux mycorrhiza caused no growth stimulation even in three low-phosphate soils. At 18° C infection was much sparser in a 6 h daylength than in 12 and 18 h. Mycorrhizal plants kept in daylengths of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
2
3

Year Published

1981
1981
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(70 citation statements)
references
References 21 publications
9
55
2
3
Order By: Relevance
“…Our results are consistent with many others found in the literature, which concern the benefits conferred by mycorrhizal colonization on the host plant [25,26]: mycorrhizal infection stimulated the growth of D. guianensis seedlings, and the intensity of the stimulation was clearly affected by light intensity. The extra dry matter production was greatest under medium light intensity, which also led to largest leaf area.…”
Section: Morphological Adjustment To Light Intensitysupporting
confidence: 82%
See 1 more Smart Citation
“…Our results are consistent with many others found in the literature, which concern the benefits conferred by mycorrhizal colonization on the host plant [25,26]: mycorrhizal infection stimulated the growth of D. guianensis seedlings, and the intensity of the stimulation was clearly affected by light intensity. The extra dry matter production was greatest under medium light intensity, which also led to largest leaf area.…”
Section: Morphological Adjustment To Light Intensitysupporting
confidence: 82%
“…Since that time, many investigators have reported conflicting results [25,36,44]. Interactions between mycorrhizal efficacy and light are complex because light affects plant growth not only directly through photosynthesis, but also indirectly through its effects on other factors [12,21].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient status of soil is the best studied, commonly observed experimentally (e.g. Bjorkman, and probably the most relevant environmental 1942; Hayman, 1974;Daft & El Giahmi, 1978; Son mediator of plant responses to mycorrhizal associ-& Smith, 1988). Anthropogenic pollution can alter ations.…”
Section: Defining Costs and Benefits In Mycorrhizal Systemsmentioning
confidence: 99%
“…Soil pH is a factor that normally affects the development of mycorrhizal symbiosis (17,28,31), mainly at acidic levels when the soil presents high Al + and H + contents, which are toxic to AMF (26,30) and cause the adsorption of phosphorus, making it unavailable to the plant.…”
Section: Root Colonizationmentioning
confidence: 99%